THE INFLUENCE OF PARENTING STYLE AND EMPATHY ON TEENAGER’S BULLYING BEHAVIOUR IN ISLAMIC BOARDING SCHOOL - Imas Nurjanah; Alfiasari; Nur Islamiah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Children's lives in islamic boarding schools (pesantren) that are separated from their parents and live with their guardians and friends provide their own challenges for the lives of teenagers. This study aims to analyze the effect of parenting style and empathy on adolescent bullying behavior in islamic boarding schools. The study was located in one Islamic boarding school in Sukabumi Regency which was determined purposively. The study involved 90 students who were selected using proportional random sampling. The results showed that there were significant differences between male and female students in bullying behavior as perpetrators and victims. The results of the relationship test found that the dimensions of father and mother's rejection had a significant positive relationship with bullying behavior as perpetrators, while the mother's support dimension had a significant negative relationship with bullying behavior as perpetrators. The results of the relationship test also found that the parenting styles of fathers, mothers, and caregivers in islamic boarding schools had a significant positive relationship with student empathy. The results of the influence test found that father's parenting style, mother's parenting style, and empathy had a significant negative effect on bullying behavior as perpetrators. In addition, the length of stay in the islamic boarding school has a significant negative effect on bullying behavior as a victim.